The influence of stomach distention on feeding in the nudibranch mollusk Melibe leonina. Issue 4 (3rd July 2016) - Lee, Colin A.; Watson, Winsor H.
Abstract: Although research on satiation has revealed much about the effect of sensory inputs on motivational state, we have yet to fully understand exactly how satiating signals influence the neural circuits underlying specific behaviors. One organism that is well suited for addressing this question is the nudibranch Melibe leonina, because its feeding activity is easily quantified, it has translucent skin that makes the stomach easy to observe, and it has large, identifiable neurons that are very suitable for subsequent analysis of the neural correlates of satiation. In this study our goal was to document the time course of satiation in Melibe, and determine if stomach distention contributes to satiation. When exposed to brine shrimp ( Artemia ), Melibe immediately commenced stereotypic oral hood movements to capture prey, and continued to do so for approximately five hours. Individuals eventually stopped, despite the continued presence of food, and the slowing and eventual termination of oral hood closures was correlated with distension of the stomach caused by the ingested Artemia . We obtained further evidence that stomach distension is one of the underlying causes of satiation by injecting artificial non-nutritive food into the stomach, and by cutting open part of the stomach wall to prevent it from filling and distending. The first treatment caused satiation to occur more rapidly, while the second treatment delayed satiation. Both results demonstrate that in Melibe stomach distention has a major impact on the motivation to feed. These findings provide the framework for subsequent studies designed to determine precisely how stomach distention influences feeding circuits.